Queuing System Analisis And Optimazation Of Billiard Profits In Lobusona Village - Domo, Alfun Khoir; Tanjung, Eka Agustin; Ramadhani, Ramadhani; Ritonga, Irmayanti (Journal of Student Development Information System (JoSDIS), 2024)
A queue is a waiting line of players (one or more) which requires a waiting time of 30 minutes or more. Because in reality, queues are caused by waiting times that are longer than playing times. The aim of this research is to analyze the application of the M/M/S model to the Billiards queuing system in Lobusona village. The first step taken was to collect billiard queue arrival data. The results of calculations using the M/M/S model at Billiards in Lobusona village apply player queue discipline, namely first come first serve (FCFS). The player arrival pattern has a Poisson distribution and the service pattern has an exponential distribution. From the calculation results, the average number of players waiting to enter the extension system in the time period 12:00-17:00 WIT is 30,123 people or = 30 people. Meanwhile, the average number of customers waiting in the shortest system occurred in the time period 08.00 – 10.00, namely 4,838 people or 5 people. The average number of customers in the queue occurred in the time period 12.00 – 13.00, namely 5,768 people or 7 people. It can be concluded that the performance of the Lobusona Village Billiards queuing system is optimal.